Peran Katekese Pra Misa dalam Memperkuat Iman Umat Katolik - Fransiska Masandai Jawan; Intansakti Pius X (Jurnal Pendidikan Agama dan Teologi, 2024)
The pre-mass catechesis is a continuation of the apostolic tradition practiced by the Apostles. Pre-mass catechesis today has a wider understanding than ever before. This is not limited to brief teachings about the Catholic faith but also seeks to prepare Catholics spiritually, intellectually, and personally so that Catholics can attend mass more meaningfully and actively participate. The author uses data collection techniques in the form of observation and interviews. Some of the important roles of pre-mass cateteche are preparing people, deepening understanding of faith, building a strong and effective Christian community. In carrying out pre-mass catechesis does not take a long time, usually 5 to 10 minutes. Pre-Mass catechesis is a form of religious teaching that aims to prepare Catholics spiritually so that they can celebrate the Eucharist with deep understanding, active involvement, and passion. Pre-Mass catechesis is not only the delivery of information, but also the formation of the hearts of Catholics to receive Jesus Christ in the celebration of the Eucharist.